Yield and nutrient rontent of chilli (Capsicum annuum L.) in responu to sources of P ilnd levels of P and N - Josephrajkumar, A Subbiah, M Murugan, S Backiyarani, A (Journal of Spices and Aromatic Crops, 2002)
The highest yield of chilli dry pods (2770 kg ha-1) was obtained by the application of 120, 60 and 35 kg N, P2O5 and K2O ha-1. The response to N and P application was linear up to 120 and 60 kg ha-1 N and P2O5, respectively. The protein content of dry pod increased in the higher levels of N and the highest value (12.2.5%) was recorded at 120 kg ha-1. N and P application increased protein and mineral contents of dry pods. Among the sources of P, rock phosphate registered maximum calcium content compared to single super phosphate. The efficiency of incubated rock phosphate was similar to that of single super phosphate. However, rock phosphate with phosphobacteria did not enhance yield. Farm yard manure incubated rock phosphate proved to be a cheaper source of phosphatic fertilizer for soils with higher pH (>8).